2020
DOI: 10.1038/s41598-020-59543-w
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Wild Pigs as Primary Nest Predators for Wild Turkeys

Abstract: similar to natural turkey nests 34. Additionally, simulated nest studies allow for assessment of the influence of the density of nests on nest depredation 35. We used simulated wild turkey nests to evaluate the magnitude of nest predation by wild pigs relative to native nest predators throughout the nesting season in 2016. We also simulated differing densities of nests to evaluate for changes in the frequency of nest predation. Our first objective was compare the frequency of nest consumption by wild pigs to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…We predicted that armadillo and turkey spatial overlap with wild pigs would be greatest in the fall, but armadillos were instead positively associated with wild pigs in the spring and turkeys were positively associated with wild pigs in the summer. Spatial overlap with turkeys outside of nesting season may not be of great concern, but overlap should be monitored across years given the detrimental effects wild pigs could have when turkeys nest in the spring (Sanders et al, 2020). Wild pigs in our study area had low temporal overlap with turkeys, whereas higher spatial overlap between wild pigs and bobcats, raccoons, and armadillos did not appear mediated by diel activity partitioning.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We predicted that armadillo and turkey spatial overlap with wild pigs would be greatest in the fall, but armadillos were instead positively associated with wild pigs in the spring and turkeys were positively associated with wild pigs in the summer. Spatial overlap with turkeys outside of nesting season may not be of great concern, but overlap should be monitored across years given the detrimental effects wild pigs could have when turkeys nest in the spring (Sanders et al, 2020). Wild pigs in our study area had low temporal overlap with turkeys, whereas higher spatial overlap between wild pigs and bobcats, raccoons, and armadillos did not appear mediated by diel activity partitioning.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research suggests the occurrence (O'Brien et al, 2019) and abundance (Stevens, 1996) of coyotes and wild pigs are positively correlated, but the only significant relationship we found between coyote site use and wild pig activity was a negative one in the fall. Although farrowing occurs throughout the year, most wild pigs in our study area were likely born in the winter and spring (VerCauteren et al, 2020), so we would expect wild pig activity to have a positive effect on coyote site use during these seasons if wild pigs benefit coyotes. However, Keiter et al (2017) and Chinn et al (2021) documented fairly low coyote predation on juvenile wild pigs in South Carolina, and concurrent research in our study area found that wild pig was a minor component (≤5%) of coyote diet across seasons (Jensen et al, In review).…”
Section: Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…We alternated different egg sizes and egg‐shell patterns (affecting egg visibility and palatability: Castilla et al ., 2007) because they may be differently targeted by predators (Svobodová et al ., 2012; Bravo et al ., 2020). During all artificial nest deployment operations, we wore clean boots and latex gloves while handling equipment, to minimize the addition of human scent (Arbeiter & Franke, 2018; Sanders et al ., 2020). Artificial nests may be more attractive to predators than natural ones, because they are often placed on trails, and because of the absence of adults defending, the clutch may increase predation rate (Bravo et al ., 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Nest destruction by wild boar has been assessed by recording rooting activity and signs of presence around nests after egg hatching (Henry, 1969; Crome & Moore, 1990; Campos, 1993; Fordham et al ., 2006; Padyšáková et al ., 2011; Kambourova, 2012; Baccetti & Puglisi, 2013; Sanders et al ., 2020), by analyzing tooth marks on plasticine eggs in artificial nests (Wood & Barrett, 1979; Duarte & Vargas, 2001; Purger & Meszaros, 2006; Purger et al ., 2008; Padyšáková et al ., 2011; Svobodová et al ., 2012; Carpio et al ., 2014, 2016; Senserini & Santilli, 2016), or anecdotally reported (Stegeman, 1938; Challies, 1975; Pavlov et al ., 1992). In one case, a nest with young birds was found in the stomach of a killed wild boar (Giménez‐Anaya et al ., 2008).…”
Section: Introductionmentioning
confidence: 99%